Head and neck neoplasm: Main causes and treatments (Research, Society and Development, 2021)
The term head and neck cancer (CCP) refers to a group of heterogeneous tumors that affect the upper gastrointestinal tract, the main histological type of which is squamous cell carcinoma, responsible for about 90% of cases. The work aims to expose through the analysis of scientific articles the main causes and treatments associated with neoplasia of the head and neck. This is a qualitative bibliographic review based on scientific production based on studies already published between the years 2017 to 2021. In head and neck cancer, genetic and environmental risk factors contribute to its etiology, such as drinking and smoking, which are the most relevant risk factors for diseases of the upper gastrointestinal tract. With regard to thyroid cancer, there are multiple reasons considered to be risk factors, namely radiation exposure, hormonal conditions, obesity, family history of cancer and ingestion of iodized foods. Treatments for these types of cancer can include surgical resection, chemotherapy, radiation therapy, hormonal therapy or a combination of multiple treatment modalities, resulting in changes in function and quality of life. More in-depth scientific studies are needed on this cancer and the development of preventive measures for the general population, making them aware of how smoking, alcohol consumption and HPV infection can be causes for the development of this malignant neoplasm.